TINJAUAN YURIDIS TINDAK PIDANA FISKAL DALAM HUKUM PAJAK DI INDONESIA - Wulan Dewi, Ni Luh Putu Mas Arya; Trisna Dewi, Putu Eka; Laksmi Dewi, Cokorde Istri Dian (Universitas Mahendradatta, 2025)
–Tax law must provide strict legal guarantees and justice, both for the state as the tax collector (fiscus) and for the people as taxpayers. Tax crimes in a country cannot be avoided. One of the tax crimes is fiscal crime. The approach method used in this legal research is normative juridical. This is done by analyzing primary legal materials, secondary legal materials and tertiary legal materials using normative and qualitative juridical analysis, then arranged systematically. Tax crimes are also referred to as crimes in the economic sector because taxation is related to income and expenditure that affect the economy in general. Tax crimes can harm the state financially, disrupt the economy, and hinder national development. The government can set sanctions for taxpayers who do not pay taxes or deliberately refuse to pay taxes.